Global Climate Governance, Short-Termism, and the Vulnerability of Future Generations. Issue 2 (2022) - Caney, Simon
Abstract : Abstract: Many societies are now having to live with the impacts of climate change and are being confronted with heat waves, wildfires, droughts, and rising sea levels. Without radical action, future generations will inherit an even more degraded planet. This raises the question: How can political institutions be reformed to promote justice for future generations and to leave them an ecologically sustainable world? In this essay, I address a particular version of this question; namely: How can supra–state institutions and transnational political processes be transformed to realize climate justice for future generations? The essay seeks to make two contributions. First, it considers what criteria should guide the evaluation of proposals for reform. It proposes four criteria, and analyzes how they should be interpreted and applied. Second, it considers a raft of different proposals, commenting on their strengths and weaknesses. It presents ten proposals in all, including, among others, establishing a UN high commissioner for future generations, appointing a UN special envoy for future generations, creating a UN agency mandated to protect future generations, instituting representatives for the future in all key UN bodies, ensuring greater youth participation in transnational political decision-making processes, and further developing a global citizens' assembly. In short, my aim is to outline some of the options available and to defend a normative framework that we can use to evaluate them.